Statistical analysis of TEC perturbations over a low latitude region during 2009–2013 ascending solar activity phase - Andima, Geoffrey; Jurua, Edward; Amabayo, Emirant Bertillas; Habarulema, John Bosco (Advances in Space Research, 2015)
Total Electron Content (TEC) perturbations are manifestations of ionospheric irregularities which induce fluctuations in the amplitude and phase of trans-ionospheric radio signals. TEC data derived from Global Positioning System (GPS) receivers at Mbarara (Geogra. 0.60 N, 30.74 E and Geomag. 10.22 N, 102.36 E) and Entebbe (Geogra. 0.04 N, 32.44 E and Geomag. 9.53 N, 104.10 E) from 2009 to 2013 were used to study TEC perturbations over the low latitude region of Uganda. The results show that the frequency of occurrence of TEC perturbations of >4 TECU increased steadily from 2009 to 2013. TEC perturbations with amplitude <4 TECU occurred at all times. The likelihood of TEC perturbations exceeding 6 TECU was higher during the equinoxes than during the solstices in most of the years. Comparison of TEC perturbations with 10.7 cm solar radio flux (F10.7) data showed a weak positive correlation with this solar proxy. Wavelet analysis performed on the TEC perturbations revealed wave-like oscillations with periods typical of Traveling Ionospheric Disturbances (TID). These wave-like structures (WLS) dominated from 13:00 to 19:00 LT for most of the years analyzed.
Keywords: Total Electron Content; Low-latitude TEC perturbations; Traveling Ionospheric Disturbances